PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING TERINTEGRASI EKSPLORASI GEOGEBRA UNTUK MAMFASILITASI KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKAPESERTA DIDIK KELAS XI - Felisa, Dhea Ika; Arfinanti, Nurul (Universitas Jenderal Soedirman, 2024)
This research aims to develop student worksheets (LKPD) based on Discovery Learning integrated with GeoGebra exploration to facilitate class XI students' ability to understand mathematical concepts in circle material. This development research uses the ADDIE development model. Research subjects included material and media experts, consisting of mathematics education lecturers and mathematics teachers, as well as 36 students in class XI Phase FD2 at SMA Negeri 2 Banguntapan as small-scale trial subjects. The analysis techniques used include analysis of product validity, practicality and effectiveness. The research results show that the GeoGebra integrated Discovery Learning based LKPD has a validity of 88.3% in the very valid category, practicality of 78.75% in the practical category, and effectiveness of 88% in the very good category. Thus, this LKPD is suitable for use in learning because it meets the criteria of being valid, practical and effective.